Effect of boron on yield and quality of groundnut (Arachis hypogaea) on lateritic soil - MAHAJAN, T S; CHAVAN, A S; DONGALE, J H (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during the winter seasons (rabi) of 1988-89 and 1989-90 on lateritic soil to study the effect of boron on yield and quality of 'SB 11' groundnut (Arachis hypogaea L.). The treatments were: T1, no boron; T2, soil application of n @ 0.5 kg/ha through horonaled superphosphate; T3, 0.5 kg/ha through borax.; 14, 1.0 kg/ha through borax; T5, 1.5 kg/ha through borax; and T6, B @ 0.5 ppm in Z foliar sprays. Treatment T2 gave significantly higher yield of dry pods (3200 kg/ha) and harvest index (42.84) than all other treatments. It also gave significantly higher yield of oil (1 156 kg/ha) and protein (659 kg/ha) and showed higher uptake of nitrogen (127.4 kg/ha) and phosphorus (11.7 kg/ha) in-kernels than T2, T3, T4 and T5.